The Effectiveness of Information Services by Using the Drama Film "Cry Me A Sad River" to Minimize Bullying Behavior in Middle School Students - Lestari, Yuli; Siregar, Alfin (Journal for Lesson and Learning Studies, 2023)
The background of this research is the phenomenon regarding the rise of bullying cases in schools. The high bullying behavior in students encourages providing a service as an information service. This research aimed to test the effectiveness of information services using the drama film "try me a sad river" to minimize bullying behavior in junior high school students. The method used is quantitative, with the type of research used is Quasi-Experimental with a Non-Equivalent Control Group Design. The total population of the study was 84 students of eighth-grade junior high school. The research sample was selected using a purposive sampling technique with the criteria of high bullying behavior. Data collection techniques in this study used bullying behavior scale instruments and interviews. The research instrument used the Likert Scale model, then analyzed using an independent sample t-test with SPSS. The study results show that information services using the drama film "cry me a sad river" effectively minimize the bullying behavior of junior high school students.